Effects of RF plasma treatment on spray-pyrolyzed copper oxide films on silicon substrates. (15th November 2017) - Madera, Rozen Grace B.; Martinez, Melanie M.; Vasquez, Magdaleno R.
Abstract: The effects of radio-frequency (RF) argon (Ar) plasma treatment on the structural, morphological, electrical and compositional properties of the spray-pyrolyzed p-type copper oxide films on n-type (100) silicon (Si) substrates were investigated. The films were successfully synthesized using 0.3 M copper acetate monohydrate sprayed on precut Si substrates maintained at 350 °C. X-ray diffraction revealed cupric oxide (CuO) with a monoclinic structure. An apparent improvement in crystallinity was realized after Ar plasma treatment, attributed to the removal of residues contaminating the surface. Scanning electron microscope images showed agglomerated monoclinic grains and revealed a reduction in size upon plasma exposure induced by the sputtering effect. The current–voltage characteristics of CuO/Si showed a rectifying behavior after Ar plasma exposure with an increase in turn-on voltage. Four-point probe measurements revealed a decrease in sheet resistance after plasma irradiation. Fourier transform infrared spectral analyses also showed O–H and C–O bands on the films. This work was able to produce CuO thin films via spray pyrolysis on Si substrates and enhancement in their properties by applying postdeposition Ar plasma treatment.